Pengembangan Wisata Bahari di Wilayah Pesisir Kecamatan Pulo Aceh, Kabupaten Aceh Besar - Mumtadul Fikri; Khursatul Munibah; Fredinan Yulianda (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
Pulo Aceh is an island district in Aceh Besar District, which is located at the western tip of the island of Sumatra. Pulo Aceh District has marine tourism potential that has not been fully developed. The main objective of this research is to plan the development of coastal areas based on the concept of marine tourism in order to formulate directions for the development of marine tourism in the coastal area of Pulo Aceh District. The method used is the survey method and descriptive analysis to analyze the suitability of marine tourism, the carrying capacity of the area and the level of community willingness, by collecting data through spatial approaches and interviews. The results of the analysis show that there are 6 villages that can be developed as snorkeling and diving tourism destinations in the coastal area of Pulo Aceh District with a high level of community willingness. Development is based on descriptive analysis, with the following priority directions: (1) maximizing the development of potential, carrying capacity and community participation to make marine tourism management sustainable; (2) formulate and implement policies for spatial use regulations based on resource potential by involving local communities in monitoring marine tourism activities; (3) improve facilities and infrastructure as well as supporting facilities for the development of marine tourism.